Distinct Roles of Two Histone Methyltransferases in Transmitting H3K36me3-Based Epigenetic Memory Across Generations in Caenorhabditis elegans. Issue 3 (14th September 2018) - Kreher, Jeremy; Takasaki, Teruaki; Cockrum, Chad; Sidoli, Simone; Garcia, Benjamin A; Jensen, Ole N; Strome, Susan
Abstract: Epigenetic information contributes to proper gene expression and development, and can be transmitted not only through mitotic divisions but also from parents to progeny. We investigated the roles in epigenetic inheritance of MES-4 and MET-1, the two Caenorhabditis elegans enzymes that methylate H3K36 (histone H3 Lys 36). Mass spectrometry analysis confirmed immunostaining results showing that both MES-4 and MET-1 catalyze H3K36me3. In the adult germline, MES-4 is enriched in the distal mitotic zone and MET-1 is enriched in the meiotic pachytene zone. Embryos inherit H3K36me3-marked chromosomes from both the oocyte and sperm, and a maternal load of MES-4 and MET-1 . Maternal MES-4 quickly associates with sperm chromosomes; that association requires that the sperm chromosomes bear H3K36me3, suggesting that MES-4 is recruited to chromosomes by preexisting H3K36me3. In embryos that inherit H3K36me3-positive oocyte chromosomes and H3K36me3-negative sperm chromosomes, MES-4 and H3K36me3 are maintained on only a subset of chromosomes until at least the 32-cell stage, likely because MES-4 propagates H3K36me3 on regions of the genome with preexisting H3K36me3. In embryos lacking MES-4, H3K36me3 levels on chromosomes drop precipitously postfertilization. In contrast to the relatively high levels of MES-4 in early-stage embryos, MET-1 levels are low at early stages and start increasing by the ∼26-cell stage, consistent with expression from the zygotic genome. Our findings support the model that MET-1 mediates transcription-coupled H3K36me3 in the parental germline and transcriptionally active embryos, and that MES-4 transmits an epigenetic memory of H3K36me3 across generations and through early embryo cell divisions by maintaining inherited patterns of H3K36me3.